Intensive Care Society's APACHE II study in Britain and Ireland–I: Variations in case mix of adult admissions to general intensive care units and impact on outcome. Issue 6910 (16th October 1993) - Rowan, K M; Kerr, J H; Major, E; McPherson, K; Short, A; Vessey, M P
Abstract : OBJECTIVES–To describe the extent of variation in the case mix of adult admissions to general intensive care units in Britain and Ireland and investigate the impact of such variation on outcome. DESIGN–Prospective, cohort study of consecutive admissions to intensive care units. SETTING–26 general intensive care units in Britain and Ireland. SUBJECTS–9099 admissions to the intensive care units studied. MAIN OUTCOME MEASURE–Death or survival at discharge before and after adjustment of case mix (age, history of chronic conditions, surgical status, diagnosis, and severity of illness) according to the APACHE II method. RESULTS–Important differences in case mix were found, with large variations between the units. Hospital mortality was significantly associated with most of the case mix factors investigated. CONCLUSIONS–Comparing crude death rates in hospital between intensive care units may be misleading indicators of performance. The collection of data on case mix needs to be standardised and differences in case mix adjusted for when comparing outcome between different intensive care units.